STRATEGI PENINGKATAN KETAHANAN SOSIAL EKONOMI DESA MELALUI SISTEM EKONOMI GOTONG ROYONG BERBASIS BADAN USAHA MILIK DESA - Mundayat, Aris Arif; Yuhastina, Yuhastina; Narendra, Bagas; Gufronudin, Gufronudin (UNIVERSITAS SEBELAS MARET (UNS), 2022)
AbstractThis article is an analysis of the potential of the Mutual Cooperation Economic System (MCES) based on social capital and inclusive cooperation to increase social resilience through BUMDes (Village Owned Enterprises). The village's socio-economic resilience is crucial to review. It is considering that the number of villagers in the last 50 years has decreased up to more than 50%. Villages seem to lose their productive force due to the process of urbanization interm of horizontal mobility from rural to urban at the national, regional, and global levels, This situation generates economic pressure to the rural areas as a process of integrating villagers into market citizens. Then the second factor is the spatial urbanization characterized by the integration of the village with the city in terms of space and lifestyle. In this situation, village loses its socio-economic resilience because its productivity tends to decrease. Then pandemic Covid-19 has made the industrial sector laidoff their workers who then returned to villages. The percentage of poverty rate increased from 9.22 percent in September 2019 to 10.14 percent in March 2021. It shows that rural area losses their socio-economic resilience because their productivity tends to decline. This study uses a qualitative research method by conducting observations and Focused Group Discussion with the management to analyze the social-economic potential of the BUMDes Tirtamas Kapanewon, Mlati, Sleman Regency and other BUMDes network as the unit of the study. This study shows that BUMDes Tirtamas has the potency to develop MCES by building a mutual network with Smal and Micro Enterprises included other BUMDes from other villages building a Mutual Cooperation Economic System. The contribution of new ideas is in this study is the idea of Mutual Cooperation Economic System (MCES) as an alternative economy system to coexists with the neoliberal market economy.Key Word: Sosial-Ekonomi, Resilience, Mutual Cooperation, Citizen, VOEs, Neoliberal. AbstrakArtikel ini merupakan analisis potensi Sistem Ekonomi Gotong Royong (SEGORO) berbasis modal sosial dan kejasama inklusif untuk meningkatkan ketahanan sosial melalui BUMDes (Badan Usaha Milik Desa). Ketahanan sosial ekonomi desa sangat penting untuk ditinjau. Mengingat jumlah penduduk desa dalam 50 tahun terakhir telah berkurang hingga lebih dari 50%. Desa seolah-olah kehilangan tenaga produktifnya akibat proses urbanisasi karena mobilitas horizontal dari desa ke kota di tingkat nasional, regional, dan global. Kemudian faktor kedua adalah urbanisasi spasial yang ditandai dengan integrasi desa dengan kota dari segi ruang dan gaya hidup. Dalam situasi ini desa kehilangan ketahanan sosial ekonominya karena produktivitasnya yang cenderung menurun. Kemudian pandemi Covid-19 pun membuat sektor industri mem-PHK pekerjanya yang kemudian kembali ke desa. Persentase angka kemiskinan meningkat dari 9,22 persen pada September 2019 menjadi 10,14 persen pada Maret 2021. Penelitian ini menggunakan metode penelitian kualitatif dengan melakukan observasi dan Focused Group Discussion bersama pihak manajemen untuk menganalisis potensi sosial ekonomi BUMDes Tirtamas Kapanewon, Mlati, Kabupaten Sleman dan jaringan BUMDes lainnya sebagai unit kajian. Kajian ini menunjukkan bahwa BUMDes Tirtamas memiliki potensi untuk mengembangkan SEGORO setelah membangun jaringan gotong royong dengan Usaha Kecil dan Mikro termasuk BUMDes lain dari desa lain yang membangun Sistem Ekonomi Gotong Royong. Kontribusi berupa ide baru dari kajian ini adalah ide SEGORO sebagai sistem ekonomi alternatif yang hidup berdampingan dengan ekonomi pasar neoliberal.Kata Kunci: Sosial-Ekonomi, Ketahanan, Gotong Royong, BUMDes, Neoliberal.